Indoleninyl-substituted pyrimido[1,2-b]indazoles via a facile condensation reaction - Ramle, Abdul Qaiyum; Fei, Chee Chin; Tiekink, Edward R. T. *; Basirun, Wan Jefrey (Royal Society of Chemistry, 2021)
A new series of pyrimido[1,2-b]indazoles bearing indolenine moieties was synthesized through a simple condensation reaction with up to 94% yield. The present method features the versatile formation of a pyrimidine ring with a broad range of substrates, great functional group compatibility and facile synthetic operation. The work offers opportunities in drug development as well as in materials science